Anthropology - Miller Barbara D; Wood Bernard (Boston Pearson, 2006)
This text presents the core concepts of anthropology from the unique voices of the four fields using current discoveries, research and issues to demonstrate how the issues and perspectives are connected and why anthropology is relevant to today's world.
Keywords: Social anthropology